EVALUASI BAHAN BAKU INDUSTRI ARANG DI KESATUAN PEMANGKUAN HUTAN (KPH) TANJUNG PINANG - Boen M Purnama; Subandi Subandi (Jurnal Penelitian Hasil Hutan, 1988)
The  appraisal  of  charcoal  raw  material  was conducted   in  Tanjung  Pinang,  Province  of  Riau.   The  study   showed that  Bakau  (Rhizophora sp.)   is the only  species  used  for  charcoal making, whereas, Nyirih (Xylocarpus sp.) is widely used as starting fuel.                                                                                                                                The amount  of  bakau wood  required per kiln per batch  was 71.1ton.  Rough  estimate  on total  bakau wood  required per year  was 178,515 cu.m., while  available raw material only  43,181  cu.m/year. There seems to be a remarkable  shortage of  raw material of  this  time.  Most  of  the  charcoal manufacturer,  at the time  of survey,  adjust  the production capacity  by reducing  the number  of operation  or by obtaining  new raw material from  neibouring  areas